2018
DOI: 10.1177/1558689817751774
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing and Conceptualizing Quality in Mixed Methods Research: A Multiple Case Study of the Disciplines of Education, Nursing, Psychology, and Sociology

Abstract: The purpose of this qualitative multiple case study is to describe and compare how researchers in the education, nursing, psychology, and sociology disciplines operationalize and conceptualize the quality of mixed methods research (MMR). An international sample of 44 MMR researchers representing these four disciplines were interviewed. The study findings point to (a) two perspectives from which the quality of MMR is understood, one contingent and flexible and the other universal and fixed; (b) a relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…The first criterion on the relevance of (Table 4, criteria #6, 9, 11). For the MMAT, we retained the criterion #6 (quantitative and qualitative components of the study are effectively integrated) because it was also mentioned in other studies as among the most prevalent criterion for assessing the quality of mixed methods studies [17,29]. Also, some experts suggested avoiding the reference to qualitative and quantitative components in the formulation of the criteria.…”
Section: Mixed Methods Studies Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The first criterion on the relevance of (Table 4, criteria #6, 9, 11). For the MMAT, we retained the criterion #6 (quantitative and qualitative components of the study are effectively integrated) because it was also mentioned in other studies as among the most prevalent criterion for assessing the quality of mixed methods studies [17,29]. Also, some experts suggested avoiding the reference to qualitative and quantitative components in the formulation of the criteria.…”
Section: Mixed Methods Studies Criteriamentioning
confidence: 99%
“…Other terms were suggested such as legitimation, validity credibility, and integrity. To avoid entering into a semantic debate, we decided to reformulate this criterion based on the work of F abregues, Par e, and Meneses [29]: The different components adhere to the quality criteria of each tradition of the methods involved. As mentioned earlier, the MMAT was conceived as a building block.…”
Section: Mixed Methods Studies Criteriamentioning
confidence: 99%
“…Furthermore, Hurmerinta-Peltomaki and Nummela (2006) found that in the field of business, mixed methods add value by increasing validity in the findings, informing the collection of the second data source, and assisting with knowledge creation. Gibson (2017) suggested the concept of ''methodological fit'' (p. 6) between method and research question as being a potential driver of the increase in impact and rigor of a mixed methods study, suggesting that authors should analyze their research question, the current state of the literature, as well as their intended theoretical contributions when deciding to do mixed methods work. Gibson goes on to propose that mixed methods research tend to offer four main values to researchers: elaboration, generalization, data integration, and interpretations.…”
Section: Definitions Of Mixed Methods and Mixed Methods In Managementmentioning
confidence: 99%
“…If all quality must be viewed through the lens of the discipline in which the study is conducted, and if key aspects of quality are related to a subjective concept like ''trustworthiness,'' how can an integrated definition of quality be created that will hold across disciplines? Fàbregues et al (2018) make headway on this question, as their results show that there are at least two perspectives currently held toward quality, and that these perspectives are related to the discipline of the researcher interviewed. Rather than expand this discussion of quality, we narrow our focus to solely that of rigor in an effort to provide a foundation for further quality discussions.…”
Section: Defining Rigorous Mixed Methodsmentioning
confidence: 99%
“…This study was part of a larger multiple case study on the operationalization and conceptualization of the quality of MMR in the education, nursing, psychology, and sociology disciplines (Fàbregues, Paré, & Meneses, 2018). In this article, we report on the within-case analysis for the discipline of nursing.…”
Section: Methodsmentioning
confidence: 99%